Desarrollo de las raices "activas" del girasol bajo condiciones de sequia - Gonzalez-Fernandez, P.=700 1 Caballero-Ungria, F.; Miralles-Imperial, R.; Sanz-Izquierdo, J.
(Es, En)
ilus., 15 ref.
Keywords: HELIANTHUS ANNUUS; RAICES; ANATOMIA DE LA PLANTA; ESPAÑA; GIRASOL; DESARROLLO RADICULAR; CICLO VEGETATIVO